Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan UMKM Penjualan Telur Ayam Di Jalan Tempuling - Mey Yunanda; Noni Artiya Syahputri; Pratiwi Ayu Ningtyas; Zainarti Zainarti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study examines the factors that influence the income of MSMEs selling chicken eggs on Jalan Tuamang Medan. The livestock industry, especially raising hen farming, plays an important role in the economy and national food security by providing affordable and easily accessible sources of animal protein to the public. The study was conducted using observation and interview methods with egg traders who have been operating for several years. The results of the study indicate that factors such as product quality, sales location, marketing strategy, and consumer perceptions of the health and hygiene value of the product affect the income level of these MSMEs. In addition, the success of farmers in using available resources and expanding marketing networks through various channels also contributes to increasing income. Thus, strengthening marketing strategies and innovation in livestock management are the main keys to increasing the success and welfare of MSMEs selling chicken eggs in the area.